Sensoriamento remoto aplicado ao estudo do comportamento espectral da água no reservatório Passo Real - RS - Trentin, Aline Biasoli (2009)
The building of reservoirs for energy generation and water flow control generated river environmental changes as well as modifications on fluvial environment. In such context, remote sensing is a tool that enables spatial analysis and temporal aquatic environmental information acquisition. This research present a study on water spectral behavior in Passo Real reservoir, that is located in the Jacuí River watershed, in Rio Grande do Sul state, Brazil. Such study aims to evaluate leading factors to water spectral differences. The methodology comprehends spectral data collection on field by the use of spectroradiometer in September 2008; orbital data collection by Landsat satellite image in April 2009 and limnological data in September 2008, February, April and June 2009 ( total of sediments in suspension (TSS), Chlorophyll-a (Chl-a), Secchi disk (SD), hydrogenionic potential (pH), electrical conductivity (EC), organic carbon (CO) and water temperature. Besides that, one realized a simulation of spectral answers based on limnological data. The results show that the distribution of limnological variables is in accordance with the times of the year and reservoir sections. One noticed that water transparency is in an inverse proportionality in relation to solids in suspension, taking into account that such variables are quite related to reservoir sections, mainly, to tributary that are close to dike areas. The presence of solids in suspension in the Jacuí River has mainly reflected in water reflectance that was observed in field specters and orbital data. However, correlations between limnological and field spectral data appeared to be less meaningful, once the best correlations were found between orbital and limnological data. Nevertheless, both groups of data (spectra field and orbital) exhibited the same trend to results. In sum, the use of field spectral and orbital data is an important tool that may be used as a possible solution for the analysis of reflectance appearance of the water and its relationship with limnological data.